Cigarette Displays Around the School Area and Cigarette Sales in the School Area - Fitri Hayati; Putra Apriadi Siregar; Nurhayati Nurhayati; Nasri Mohammed; Abdillah Ahsan; Syafran Arrazy (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The tobacco industry continues to promote tobacco through cigarette displays, especially in areas easily accessible to youth and school students. One of the tactics that cigarette companies keep using is cigarette displays around the school area. This study aimed to determine the impact of cigarette displays around schools on cigarette sales in the school area. This study was conducted on cigarette sellers around schools in Medan City. This study was conducted on 18 cigarette sellers for 14 days. The interventions given were cigarette displays covered with cloth, cigarette displays hidden, and cigarette displays without intervention. Data analysis was conducted using an ANOVA test using JASP version 17.The results showed a difference in total sales between cloth-covered displays, hidden treatments, and no intervention (ANOVA test p = 0.015). The results showed a difference in sales profit between cloth-covered displays, hidden treatments, and no intervention (ANOVA test p = 0.004). The provision of interventions on cigarette displays treated as hidden reduced average cigarette sales in cigarette stores. Intervention in cigarette displays covered with cloth reduced average cigarette sales in cigarette stores. The Medan City Government should regulate cigarette displays at cigarette stores around the school area to reduce cigarette consumption among students. The Education Office and schools should collaborate with cigarette sellers around the school area to stop the display of cigarettes and not sell cigarettes to students. Keywords: Cigarettes, Cigarette displays, Cigarette stores, School area